2018
DOI: 10.1093/aob/mcy135
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of foliar-applied Zn in sunflower (Helianthus annuus): importance of the cuticle, stomata and trichomes

Abstract: In sunflower, both the trichomes and cuticle appear to be important for foliar Zn absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 53 publications
4
77
0
Order By: Relevance
“…These findings indicate that nano-ZnO was likely absorbed in the same form as ZnSO4 -soluble Zn ions rather than as intact ZnO particles. This is in agreement with previous studies, including a similar studies of Li et al (2018) in soybean and Alexander et al (2016) found that absorption of insoluble foliar applied nutrients was limited (even for nano-scale particles). Therefore, solubility is an important factor to consider when designing foliar fertilisers.…”
Section: Comparing the Absorption Of Nano-zno And Znso4supporting
confidence: 94%
See 4 more Smart Citations
“…These findings indicate that nano-ZnO was likely absorbed in the same form as ZnSO4 -soluble Zn ions rather than as intact ZnO particles. This is in agreement with previous studies, including a similar studies of Li et al (2018) in soybean and Alexander et al (2016) found that absorption of insoluble foliar applied nutrients was limited (even for nano-scale particles). Therefore, solubility is an important factor to consider when designing foliar fertilisers.…”
Section: Comparing the Absorption Of Nano-zno And Znso4supporting
confidence: 94%
“…100 µm that had the highest Zn concentrations. These corresponded to the non-glandular trichomes of sunflower in which foliar-applied Zn accumulated to high concentrations (Li et al 2018).…”
Section: Distribution Of Zn In Yfels Analysed Using µ-Xrfmentioning
confidence: 99%
See 3 more Smart Citations